2012
DOI: 10.1016/j.eats.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

All-Arthroscopic Suprapectoral Long Head of Biceps Tendon Tenodesis With Interference Screw–Like Tendon Fixation After Modified Lasso-Loop Stitch Tendon Securing

Abstract: Arthroscopic suprapectoral techniques for tenodesis of the long head of the biceps tendon (LHB) are appropriate for the treatment of proximal biceps lesions. Several types of techniques and fixation devices have been described and evaluated in biomechanical studies regarding primary stability. In this technical note, we describe an all-arthroscopic suprapectoral technique using the 6.25-mm Bio-SwiveLock device (Arthrex, Naples, FL) for an interference screw-like bony fixation after having armed the tendon with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…2 Numerous options for surgical approach, location, and method of fixation have been investigated for biceps tenodesis in both cadaveric and clinical studies. Long head biceps tenodesis can be performed with an open [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] or arthroscopic technique 9,18-33 and can be positioned high at the entrance of the bicipital groove, in the suprapectoral location just proximal to the pectoralis major tendon, 9,16,22,30,31,34 in a subpectoral location at or distal to the pectoralis major tendon, 6,10,12,15,16,34 or in other positions, including the conjoint tendon or soft tissue tenodesis sites. 27,32,33,35 Arthroscopic suprapectoral and open subpectoral techniques are 2 common distal techniques for biceps tenodesis.…”
mentioning
confidence: 99%
“…2 Numerous options for surgical approach, location, and method of fixation have been investigated for biceps tenodesis in both cadaveric and clinical studies. Long head biceps tenodesis can be performed with an open [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] or arthroscopic technique 9,18-33 and can be positioned high at the entrance of the bicipital groove, in the suprapectoral location just proximal to the pectoralis major tendon, 9,16,22,30,31,34 in a subpectoral location at or distal to the pectoralis major tendon, 6,10,12,15,16,34 or in other positions, including the conjoint tendon or soft tissue tenodesis sites. 27,32,33,35 Arthroscopic suprapectoral and open subpectoral techniques are 2 common distal techniques for biceps tenodesis.…”
mentioning
confidence: 99%
“…9,10 Although there have been several biomechanical analyses of differing tenodesis techniques, 6,7,11,12 compelling clinical data showing the superiority of one technique over another have not yet been presented. Patzer et al 7 described a similar technique with a lasso loop Orthocord suture (DePuy Mitek, Raynham, MA) and a SwiveLock anchor (Arthrex). However, in their technique, they discussed the need for knot tying and delivering a limb of tendon into the interference screw site.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Both open subpectoral and arthroscopic tenodesis techniques have been advocated in the literature. [3][4][5][6][7][8][9] In a biomechanical study comparing these 2 techniques, Mazzocca et al 6 found no difference in cyclic loading or yield to failure using different interference screw tenodesis strategies. In addition, no clinical difference has been found between arthroscopic suprapectoral biceps tenodesis and open subpectoral biceps tenodesis.…”
mentioning
confidence: 99%
“…Aus biomechanischer Sicht ist der Goldstandard die intraossäre LBS-Tenodese mit einer resorbierbaren Interferenz-Schraube (41, 42). Diese kann arthroskopisch proximal suprapektoral (42)(43)(44), distal suprapektoral (45,46) oder mini-open subpektoral (47)…”
Section: Lbs-tenodese Oder Isolierte Tenotomieunclassified